“Not for Erich Honecker back then, nor for Angela Merkel Today, but for your own sake” – A Case Study About Voluntary Activity in Rural Areas Caught Between Socio-Political Claims and Individual Perceptions - Schwarzenberg, Tom; Miggelbrink, Judith; Meyer, Frank (Raumforschung und Raumordnung | Spatial Research and Planning, 2017)
For several years now, volunteer activity has been increasingly placed at the center of a political discourse monopolizing it for politics of dealing with socio- and spatio-political problems. It is particularly in those rural regions affected by out-migration and an ageing population that volunteering is considered an advisable way for securing local public responsibilities. Based on a critical reflection and discussion of these political positions we plead for a subject-oriented research approach in order to understand regionally problematised conditions not primarily as static parameters, but as individually negotiated aspects of everyday life. Accordingly, voluntary activity is investigated in terms of individually perceived challenges and underlying logics of action as a social practice of collaboratively organising everyday life in a shrinking rural region. Hence, using a case study conducted in the Altenburger Land in Thuringia we analyse the socially embedded negotiation of responsibilities between municipal actors and voluntary workers on the one hand and trace the influencing factors on voluntary activities considered relevant by involved actors on the other hand. Those factors include institutional and political support, municipality reforms, regional education and working conditions in the light of a problematic regional labour market, for example. Building on the results of our empirical research we finally discuss the political and analytical-conceptual implications resulting from the notion of a homogeneous community of voluntary workers and their political-strategic invocation and activation.
Keywords: Voluntary activity; Civic engagement; Shrinkage; Peripheralisation; Rural regions; Subject; Social practice